1661d Psychosocial stress at work including job insecurity – important risk factors of chd: an updated systematic review. (24th April 2018) - Siegrist, J; Li, J
Abstract : Introduction: In recent years evidence on elevated risks of coronary heart disease (CHD) due to exposure to adverse, chronically stressful psychosocial working conditions has accumulated. Exhausting demands and efforts in combination with low control and low reward at work seem to be of particular significance, augmenting physiological dysregulation of the cardiovascular system. Two theoretical models, demand-control and effort-reward imbalance, assessing these conditions, have been studied most frequently in recent past. This contribution aims at providing a synthesis of the current state of art concerning cohort studies on associations of these models with CHD. Methods: We conducted a systematic review on published and unpublished prospective epidemiologic studies estimating the relative risk of CHD as a function of either model. As results are often given for effects of single model components in addition to their summary measures this information is additionally analysed. This holds particularly true for job insecurity as this component has often been studied as a single risk factor. Reviews were conducted according to established quality criteria (PRISMA). Result: Taken together, both models were associated with a significantly elevated relative risk of CHD. Consistency of findings was higher if single components were analysed, specifically in case of low job control and high job insecurity. Moreover, the strength of associations varied according to adjustment for confounding factors, and there was limited evidence of a moderating role of socioeconomic position. Discussion: This review found support for a role of chronic psychosocial stress at work in terms of two theoretical models, demand- control and effort-reward imbalance, as risk factors of CHD. While the risk elevation was modest, the prevalence of exposure to stressful conditions at work was high, thus emphasising the relevance of findings for occupational health. Future studies should combine these models and enlarge the scope of analysis. Moreover, intervention studies are needed to strengthen the evidence base.